Systemic levels of neuropeptide Y and dipeptidyl peptidase activity in patients with Ewing sarcoma—Associations with tumor phenotype and survival. Issue 5 (11th November 2014) - Tilan, Jason U.; Krailo, Mark; Barkauskas, Donald A.; Galli, Susana; Mtaweh, Haifa; Long, Jessica; Wang, Hongkun; Hawkins, Kirsten; Lu, Congyi; Jeha, Dima; Izycka‐Swieszewska, Ewa; Lawlor, Elizabeth R.; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Ewing sarcoma (ES) is driven by fusion of the Ewing sarcoma breakpoint region 1 gene (EWSR1) with an E26 transformation‐specific (ETS) transcription factor (EWS‐ETS), most often the Friend leukemia integration 1 transcription factor (FLI1). Neuropeptide Y (NPY) is an EWS‐FLI1 transcriptional target; it is highly expressed in ES and exerts opposing effects, ranging from ES cell death to angiogenesis and cancer stem cell propagation. The functions of NPY are regulated by dipeptidyl peptidase IV (DPPIV), a hypoxia‐inducible enzyme that cleaves the peptide and activates its growth‐promoting actions. The objective of this study was to determine the clinically relevant functions of NPY by identifying the associations between patients' ES phenotype and their NPY concentrations and DPP activity. METHODS NPY concentrations and DPP activity were measured in serum samples from 223 patients with localized ES and 9 patients with metastatic ES provided by the Children's Oncology Group. RESULTS Serum NPY levels were elevated in ES patients compared with the levels in a healthy control group and an osteosarcoma patient population, and the elevated levels were independent of EWS‐ETS translocation type. Significantly higher NPY concentrations were detected in patients with ES who had tumors of pelvic and bone origin. A similar trend was observed in patients with metastatic ES. There was no effect of NPY on survival in patients with localized ES. DPP activity in sera from patients with ES did not differ significantly from that in healthy controls and patients with osteosarcoma. However, high DPP levels were associated with improved survival. CONCLUSIONS Systemic NPY levels are elevated in patients with ES, and these high levels are associated with unfavorable disease features. DPPIV in serum samples from patients with ES is derived from nontumor sources, and its high activity is correlated with improved survival. Cancer 2015;121:697–707. © 2014 American Cancer Society.